Comprehensive insights into profiles and bacterial sources of intracellular and extracellular antibiotic resistance genes in groundwater. (15th August 2022) - Yang, Yidi; Li, Haibei; Wei, Yijun; Chen, Zhengshan; Chen, Tianjiao; Liang, Yongbing; Yin, Jing; Yang, Dong; Yang, Zhongwei; Shi, Danyang; Zhou, Shuqing; Wang, Huaran; et al.
Abstract: Antibiotic resistance genes (ARGs), especially last-resort ARGs (LARGs), are receiving extensive attention as emerging environmental contaminants in groundwater. However, their prevalent intracellular and extracellular patterns and bacterial sources in groundwater remain unclear. Herein, groundwater samples were collected in Tianjin, and characterized based on the profiles of intracellular ARGs (iARGs) and extracellular ARGs (eARGs), as well as the resident bacterial communities and extracellular DNA (eDNA)-releasing bacterial communities. The quantitative real-time PCR assays showed that eARGs presented fewer subtypes than iARGs and generally displayed lower detection frequencies than the corresponding iARGs. Similarly, LARGs exhibited lower detection frequencies than common ARGs, but the total abundance showed no significant differences between them. Genes vanA and bla VIM were the observed dominant LARGs, and aadA was the observed common ARG independent of location inside or outside the bacteria. Furthermore, the top 10 phyla showed much difference between the main eDNA-releasing bacteria and the dominant resident bacteria. Proteobacteria was the predominant resident bacterial phyla while dominating the source of eDNA in groundwater. Despite representing a minor portion of the abundance in the resident bacteria, Actinobacteriota, Acidobacteriota, and Chloroflex surprisingly accounted for a large majority of eDNA release. Co-occurrence patterns among persistent ARGs, the resident bacteria, and eDNA-releasing bacteria revealed that the dominant common iARG aadA and intracellular LARGs bla VIM and vanA had significant positive correlations with Methylobacterium_Methylorubrum and Shewanella . Meanwhile, the dominant extracellular LARG bla VIM may be released by bacteria belonging to at least five genera, including Ellin6067, Bifidobacterium, Blautia, Veillonella, and Dechloromonas . Collectively, the findings of this study extend our understanding regarding the distribution of ARGs and their bacterial sources in groundwater, and indicate the serious pollution of LARGs in groundwater, which poses potential risks to public health. Graphical abstract: Image 1 Highlights: eARGs presented fewer subtypes and lower detection frequencies than iARGs. No significant difference was noted in the abundance of the common ARGs and LARGs. Gene aadA was detected as dominant in common ARGs, while vanA and bla VIM in LARGs. Proteobacteria was dominant in both the resident and eDNA-releasing phyla.